1996
DOI: 10.1056/nejm199605163342006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Black and Hispanic Physicians in Providing Health Care for Underserved Populations

Abstract: Black and Hispanic physicians have a unique and important role in caring for poor, black, and Hispanic patients in California. Dismantling affirmative-action programs as is currently proposed, may threaten health care for both poor people and members of minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
439
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 762 publications
(456 citation statements)
references
References 12 publications
15
439
0
2
Order By: Relevance
“…Racial matching (minority doctors seeing proportionately more patients of their own race or ethnicity) has been extensively documented in the empirical health literature. After controlling for residential composition of the population, Komaromi et al (1996) find a large and significant effect of doctor race on the racial profile of patients. Stinson and Thurston (2002) find that in ZIP codes where fewer people speak English, Hispanic doctors have more Hispanic patients than non-Hispanic patients.…”
Section: Health Care Markets and The Long-term Effects Of Prejudicementioning
confidence: 88%
“…Racial matching (minority doctors seeing proportionately more patients of their own race or ethnicity) has been extensively documented in the empirical health literature. After controlling for residential composition of the population, Komaromi et al (1996) find a large and significant effect of doctor race on the racial profile of patients. Stinson and Thurston (2002) find that in ZIP codes where fewer people speak English, Hispanic doctors have more Hispanic patients than non-Hispanic patients.…”
Section: Health Care Markets and The Long-term Effects Of Prejudicementioning
confidence: 88%
“…The influence of physician-patient racial and ethnic concordance on patient care has been consistently documented for decades, [16][17][18][19][20] and may partially explain some of the disparities found. Previous studies have demonstrated that despite their best efforts, physicians sometimes struggle to perform as unbiased operators, often allowing their own cultural and social constructs to partially dictate their approach to patient care, including their medication prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…A 2001 survey of medical-school graduates showed "striking differences" between the views of minority and non-minority respondents on societal issues, with much higher percentages of minorities than non-minorities expressing strong agreement with the views that "access to health care continues to be a major problem"; "everyone is entitled to receive adequate medical care"; and "physicians can influence health and disease and prevention" (AAMC, 2002, p. 50). Studies also have found that minority physicians are more likely than non-minority physicians to practice in areas with a shortage of physicians or a higher proportion of residents from underserved minority groups, and are more likely to care for minority, indigent, and uninsured patients (AAMC, 2002;Komaromy, et al, 1996;Keith, et al, 1985;Moy & Bartman, 1995). As members of the minority and the medical communities, moreover, physicians of color can "play a key role" in "hold[ing] the system accountable" (Sullivan Commission, 2004, p. 18).…”
Section: Less Pressure For System Changementioning
confidence: 99%